The chinese mask: notes on the use of sources produced by the Brazilian military dictatorship’s repression apparatus (Tempo e Argumento, 2010)
The methodological aspects which the historians face when using documents produced by the Brazilian military dictatorship on the leftist movements which intended to trigger the revolutionary struggle are analyzed. Whereas the strategy of the repressive regime in producing and establishing the ‘truth’ is enhanced, the resistance strategies of the political forces targeted by the repressive apparatus are investigated. The documents on the political organization called Marxist-Leninist Popular Movement have been employed.
Keywords: Marxist-Leninist Popular Movement; brazilian military dictatorshi; Maoism in Brazil; brazilian Left; historical sources